PERBEDAAN KADAR KAFEIN DAUN TEH (Camellia sinensis (L.) Kuntze) BERDASARKAN STATUS KETINGGIAN TEMPAT TANAM DENGAN METODE HPLC - Anif Nur Artanti; Wahyu Rohmatin Nikmah; Discus Hendra Setiawan; Fea Prihapsara (Universitas Sebelas Maret, 2016)
Tea is the most widely consumed beverage in the world next to water. Tea leaves contain caffeine compound that has many advantages for health. Generally tea garden is in hill, especially in the mountain area which has difference high place that can influence the secondary metabolic compound in plant. So, it needs to observe about the effect of difference height planting place to tea leaf caffeine contain. This research was experimental research that taken samples from tea leaf TRI 2024 variety from 3 height variations, is 800 m; 1000 m; and 1200 m above sea level. The analytical method used in this research is high performance liquid chromatography (HPLC). The HPLC instrument is Lab Alliance brand, LC-10AT VP pump, coulomb ACE 5 C18 and UV-Vis detector at 275 nm length. The difference of caffeine content was analyzed using ANOVA.The result showed that any influence between height planting and caffeine content. Caffeine content in height 800 m above sea level is 562,20782 mg/gram sample, in height 1000 m above sea level is 239,80893 mg/gram sample and caffeine content in 1200 m above sea level is 185,93200 mg/gram. The highest caffeine contain is in height 800 m above sea level is 562,20782 mg/gram sample.